Localized protection of high aspect ratio trenches based on the anisotropy manipulation of plasma-polymerized fluoropolymer coating. (15th March 2023) - Silva de Vasconcellos, Douglas; Dailleau, Romain; Grimal, Virginie; Defforge, Thomas; Billoue, Jérôme; Gautier, Gaël
Abstract: Microelectronics, microfluidics and energy storage are among the application fields that could take advantage of the localized protection inside deep cavities or textured substrates. However, standard masking techniques used in the industry, such as photolithography, can be limited when applied to wafers with high aspect ratio topography. We have developed a maskless technique based on the anisotropy manipulation of the deposition and etching of a plasma-polymerized fluoropolymer layer, fully protecting the horizontal surfaces of deep trenches while keeping their sidewalls free of any protective layer. We were able to mask trenches with an aspect ratio up to ∼10, and depth of ∼100 μm. As a proof of concept for this localized protection technique, we demonstrate the formation of porous silicon layers (up to 8 μm in thickness) performed by anodization on these walls, while the horizontal surfaces were fully protected.